Design of a Gate-All-Around Stacked Nanosheet Differential Amplifier under Different Bias Conditions - Sousa, Jùlia C. S.; Perina, Welder F.; Martino, Joao A.; Agopian, Paula G. D. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2021)
This paper presents the DC design of a differential amplifier, an important building block on analog and mixed signal designs, utilizing the Verilog-A approach on Gate-All- Around Nanosheet (GAA-NSH) devices. The GAA-NSH is a device with two stacked silicon sheets in which the gate fully surrounds the channel, presenting the best electrostatic coupling possible for MOS technologies. The device has a 104nm effective width while having a physical width of only 15nm. The differential amplifier was designed with a VDD of 2.1V and input common mode of 1.4V, while biased in different inversion regions with gm/ID values of 5 V-1, 8 V-1 and 11 V-1. The gm/ID = 8V-1 project was compared against a FinFET differential amplifier project, showing an improvement of gain and transconductance while occupying less physical area. Higher efficiency projects (gm/ID= 11 V-1) present a higher gain while decreasing current consumption.
Keywords: Circuit design; Differential pair; Gate-all-around nanosheet